Implementasi Manajemen Kurikulum Merdeka Belajar dalam Meningkatkan Mutu Pendidikan - Isnaini Isnaini (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Quality education is education that is able to improve the quality of students by freeing them from ignorance and incompetence. With quality education, generations or human resources will be born who are superior in various aspects of life. To respond to challenges in the world of education during and after the pandemic, the government launched an independent learning curriculum program. Innovation is a new step from the government, but in its implementation, it does not change much about the essence of the previous curriculum. This program only adds new variations to support the strengthening of students' character. The research used the library research method using studies related to various existing writings or literature, whether in the form of books, journals, articles, theses, and other relevant sources originating from the internet. Research shows that in the independent learning curriculum, the administrative burden that teachers must complete is less than in the previous curriculum. The preparation of ATP is simpler but still in accordance with learning objectives, so that teachers can be more focused and effective in teaching in class. Students' learning activities in the independent curriculum are not much different from the previous curriculum, but the teaching materials prepared by the teacher are simpler. Apart from that, to shape the character of students, the time allocation in the independent curriculum is clearer and the actions taken are more concrete, which is realized through the project to strengthen the profile of Pancasila students (P5).